ANALISIS KOMPARATIF METODE TREND DALAM PERAMALAN PRODUKSI KOPI INDONESIA - Novi Permata Indah; Yusuf Muhyiddin; I Putu Eka Wijaya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Indonesian coffee production is not the largest production in Indonesia, but in  In 2020 the value of coffee exports in Indonesia occupies the 9th largest position in the world. This matter  illustrates the high economic potential of coffee production. The purpose of this study  is to analyze the best Indonesian coffee production forecasting model and  get the forecasting value of Indonesian coffee production for the next 60 years. This research  using secondary data derived from FAOstat 2022. Data used  is data on Indonesian coffee production starting from production in 1961 to production  2020. Using this data, forecasts are carried out for 60 periods, namely:  period 61-120. The analysis used is one of trend analysis (linear, quadratic).  and exponential) which has the smallest MAPE, MAD and MSD. The quadratic trend model has  MAPE is 10, MAD value is 32183, and MSD value is 1807665950 which is smaller than  other models. Therefore, it can be concluded that the quadratic linear function model  is the best model. With quadratic trend analysis, it is known that Indonesian coffee production  over the next 60 periods tends to increase. Highest production  predicted in period 120 and the smallest in period 61. The quadratic trend model is  the best model for forecasting Indonesian coffee production because it has MAPE, MAD and MSD  smallest and forecasting coffee production for the next 60 periods has a value that is  tends to increase every period.